اختلاف الإمام الكسائي مع النحاة الآخرين في النحو - Muhammad Rafif Irfan; Fakhrurozi; Ade Muhammad Ritonga; Abdulfattah Esmail Abdullah Ahmed (Arabiyyatī: Journal of Arabic Language Education, 2024)
Abstract The research question is: What are the differences between Imam Al-Kisai and other grammarians in Nahw (Arabic grammar)? This research is comparative using a qualitative approach. The comparative method aims to compare the value of one or more independent variables across two or more communities, individuals, different times, or a combination of all these factors. This research is library research, allowing the researcher to explore and analyze relevant and appropriate written sources, such as books, articles, and other documents, to support a comprehensive understanding of the research topic. The findings of this research are: The differences between Imam Al-Kisai and other grammarians in Nahw include the following issues: the subject of the noun occupied by another, whether "na'am" and "bi'sa" are verbs or nouns, the verbal nature of the style of exclamation, the permissibility of advancing the predicate of "ma zala" and similar expressions, the permissibility of conjunction before the completion of the news in the context of "inna", the factor acting on the excluded noun, the permissibility of softening the vocative triliteral if its middle letter is a vowel, the factor raising the present tense verb, the operation of "hatta", advancing the object and the subject on the conditional answer, the permissibility of advancing the object of the conditional sentence over the conditional particle, and the issue of "kuntu azunnu an al-‘aqrab" or the "Zanburiyyah" issue.   مستخلص البحث أما سؤال البحث هو: ما اختلاف الإمام الكسائي مع النحاة الآخرين في النحو.  نوع هذا البحث هو بحث مقارن باستخدام النهج الكيفي. طريقة المقارنة هي البحث الذي يهدف إلى مقارنة قيمة متغير مستقل أو أكثر في مجتمعين أو أكثر، في شخص أو أكثر، أو في أوقات مختلفة، أو في مزيج من كل ذلك. وهذا البحث هو البحث المكتبي مما مما يتيح للباحث استكشاف وتحليل المصادر المكتوبة ذات الصلة والمناسبة، مثل الكتب والمقالات والوثائق الأخرى، بهدف دعم جهود الفهم الشامل لموضوع البحث. ونتائج هذا البحث هي: أن اختلاف الإمام الكسائي مع النحاة الآخرين في النحو هو: في مسألة ناصب الاسم المشغول عنه، هل "نعم وبئس" فعلان أم اسمان؟، فعلية أسلوب التعجب، جواز تقديم خبر ما زال وما في معناها، جواز العطف في موقف إن قبل تمام الخبر، العامل في المستثنى، جواز ترخيم المنادى الثلاثي إذا كان أوسطه متحركا، عامل الرفع للفعل المضارع، عمل حتى، تقديم المنصوب والمرفوع على جواب الشرط، جواز تقديم المفعول بالجزاء على حرف الشرط، مسألة "كنت أظن أن العقرب" أو المسألة الزنبورية